Comparison of the eating quality of selected potato cultivars from two production regions in South Africa and a proposed classification system for the consumer - laryssa.booysen@gmail.com (University of Pretoria, 2013)
Dissertation (MConsSc (Food Management))--University of Pretoria,2010.